Comparative Study on Migrant Worker Management Measure of Singapore, South Korea and Taiwan - Duhamel, Pafun Nilsawas; Thammachote, Passakorn; Rattanakaset, Patrawan (Journal of Management Sciences Suratthani Rajabhat University, 2023)
International labor mobilization is on an increasing trend. Therefore, each country must have measures to manage and control the influx of workers. This research aimed to: 1) study the measures for the management of low-skilled migrant workers in Singapore, South Korea, and Taiwan; 2) Compare the measures to manage low-skilled migrant workers in Singapore, South Korea, and Taiwan. Documentary studies and in-depth interviews were used to collect data. The sample groups were selected by the head of departments in labor mobilization both in Thailand and overseas and Thai migrant workers, working in the case study’s countries. The results found that measures to manage the low-skilled migrant workers in Singapore, South Korea, and Taiwan, the "Employer-Driven" approach was used to import workers according to the needs of employers. However, to control the quantity and quality of recruiting migrant workers with efficiency and without causing economic, political, and social impacts within the country. All three countries therefore set conditions for the admission of low-skilled migrant workers in various fields, namely: entrance channel, labor qualifications such as age, language skills, and labor skills, employment ceiling, tax on foreign worker employment and employer qualifications. However, such conditions depend on the policy and socio-economic environment of each country.